Famous scholar, imam al-Ispidjabi (Journal of Philosophy Culture and Political Science, 2018)
The author of this article looks at the biography and the works of outstanding scientist al-Ispidjabi, who lived in the Middle Ages in the land of Kazakhstan. Describing his life and a century in which he lived, the author draws attention to his contribution to the culture, civilization, politics and religious situation of Central Asia in which Islam already spread and, it became a center of Islamic knowledge and science. The main purpose of this research is to acquaint readers with the unique Islamic philosopher, teacher, judge and writer al-Ispidjabi, by studying his biography and works. Al-Ispidjabi released from South Kazakhstan region, from the ancient city of Sayram (in the Middle Ages called Ispidjab). The author intended to explore the works of prominent person for future generations. Moreover, by the revival of the name of the scholar and drawing public attention to his works, he made attempt to renew our history. As one of the book of the imam al-Ispidjabi, he focused on the «SharhMukhtasar at-Tahawi».Key words: al-Ispidjabi, religion, сulture, Ispidjab, Mawarannahr, Samarkand, manuscript,Sayram, fiqh (Islamic law), judgement.